Ambient air-processed mixed-ion perovskites for high-efficiency solar cells. Issue 42 (7th October 2016) - Sveinbjörnsson, Kári; Aitola, Kerttu; Zhang, Jinbao; Johansson, Malin B.; Zhang, Xiaoliang; Correa-Baena, Juan-Pablo; Hagfeldt, Anders; Boschloo, Gerrit; Johansson, Erik M. J.
Abstract : A mixed-ion (FAPbI3 )1− x (MAPbBr3 ) x perovskite solar cell was prepared under ambient conditions with an average efficiency of 17.6%. Abstract : Mixed-ion (FAPbI3 )1− x (MAPbBr3 ) x perovskite solar cells have achieved power conversion efficiencies surpassing 20%. However, in order to obtain these high efficiencies the preparation is performed in a controlled inert atmosphere. Here, we report a procedure for manufacturing highly efficient solar cells with a mixed-ion perovskite in ambient atmosphere. By including a heating step at moderate temperatures of the mesoporous titanium dioxide substrates, and spin-coating the perovskite solution on the warm substrates in ambient air, a red intermediate phase is obtained. Annealing the red phase at 100 °C results in a uniform and crystalline perovskite film, whose thickness is dependent on the substrate temperature prior to spin-coating. The temperature was optimized between 20 and 100 °C and it was observed that 50 °C substrate temperature yielded the best solar cell performances. The average efficiency of the best device was 17.6%, accounting for current–voltage ( I – V ) measurement hysteresis, with 18.8% performance in the backward scan direction and 16.4% in the forward scan direction. Our results show that it is possible to manufacture high-efficiency mixed-ion perovskite solar cells under ambient conditions, which is relevant for large-scale and low-cost device manufacturing processing.